Association of lifestyle, dietary pattern, and liver function with cognition in older adults: findings from a cross-sectional study - Wang, Xixiang; Ren, Xiuwen; Liu, Yu; Liu, Lu; Xu, Jingjing; Zhou, Shaobo; Wang, Ying; Yuan, Linhong (Frontiers in Nutrition, 2025)
BackgroundSingle lifestyle, dietary pattern, and liver function are closely associated with cognitive ability, yet their combined influences on cognition remain unclear. This study aimed to investigate the effects of lifestyle, dietary patterns, and liver function on cognitive impairment among older adults.MethodsOne thousand and ninety-six older adults were recruited from communities. Among them, 630 participants completed cognitive function tests. The lifestyle and dietary patterns of the participants were assessed using a healthy lifestyle score (HLS) and a healthy dietary score (HDS). Liver function was assessed using four predictive indicators: AST/HDL-C, ALT/HDL-C, HSI, and ZJU. Cognitive function was measured using the Montreal Cognitive Assessment (MoCA). Logistic regression, receiver operating characteristic curves (ROC), and restricted cubic splines (RCS) were applied to explore the relationship between variables.ResultsA significant negative correlation was observed between HLS and liver function indicators (rAST/HDL-C = −0.156, rZJU = −0.270, both p < 0.001), whereas a significant positive correlation was identified between HDS and MoCA scores (r = 0.074, p < 0.05). Poor liver function, represented by elevated plasma AST/HDL-C, was associated with increased mild cognitive impairment (MCI) risk (OR = 1.029, p = 0.007). ROC analysis showed that plasma AST/HDL-C had the highest predictive power for MCI (AUC = 0.634). RCS analysis revealed that AST/HDL-C and ALT/HDL-C were positively correlated with the risk of MCI, with cut-off values of 14.1 and 10.1, respectively.ConclusionImpaired liver function is strongly associated with cognitive impairment, highlighting the critical role of maintaining healthy liver function in preventing MCI in the elderly. A healthy lifestyle positively correlated with both liver and cognitive functions, and a balanced diet significantly improved cognitive outcomes.